CARTOONS AND THE AUTOCRATIC CREEDS OF THE CULTURE INDUSTRY: VIOLENT AFFECTS AND EFFECTS IN CHILDREN’S ENTERTAINMENT - Ledesma, Jan Raen Carlo Mijaro; Manalastas, Aldrin Enciso (Sanata Dharma University, 2024)
This paper asserts that operations and patterns of violence are present in Hanna-Barbera’s Tom and Jerry, Butch Hartman’s The Fairly Oddparents, Thomas Edward Warburton’s Codename: Kids Next Door, and John Kricfalusi’s Ren and Stimpy. Cartoons are meant to be enjoyed by children. However, the incorporation of violence in cartoons can leave imprints in the impressionable minds of the children. With the media and reception of the children's audience in the foreground, the notion of false happiness can be deduced as the comedic and entertaining modes of representation in the cartoons do not just make the audience laugh but can also possibly penetrate their attitudes and behaviors. The cartoons and their violent features can be a springboard to engage media effects which can include aggression, agenda-building, and cultivation. As a framework, the discourses on violence and false happiness are supported by the critical claims of Adorno and Horkheimer on the culture industry and offshoots of immersing oneself in television. The analysis of the cartoons presented a typology of violence affirming that organized entertainment becomes synonymous with the displays of organized violence. These include blatant and forceful physical violence, subtle familial violence, violence of structural differences and tensions, and the aestheticization of violence.